Headspace single-drop microextraction of herbal essential oils - Adam, Martin; Dobiáš, Petr; Eisner, Aleš; Ventura, Karel (Journal of separation science, 2008)
A method employing the headspace single-drop microextraction (HS-SDME) is presented for the determination of essential oils in dried herbal leaves. By optimising the key experimental parameters, a linear response for the individual target compounds was obtained in the concentration range from LOQ to 4 mg/mL (r(2) = 0.9912-0.9998), with LODs from 3.3 up to 20.5 microg per 100 g of dried leaves, and the repeatability within the RSD of 2.1-8.9%. The HS-SDME-based procedure, enabling a rapid and simple analysis of essential oils in herbs, was applied to selected real samples (nine essential oils in four different samples) in combination with GC-FID identification and quantification of the target volatiles.
Keywords: financování organizované; Oils, Volatile; Financing, Organized; Temperature; Chromatography, Gas; teplota; chromatografie plynová; oleje prchavé